Instructional Models in Computer-Based Learning Environments
X, 516 p.
Keywords: In the last decade there have been rapid developments in the field of computer-based learning environments. A whole new generation of computer-based learning environments has appeared, requiring new approaches to design and development. One main feature of current systems is that they distinguish different knowledge bases that are assumed to be necessary to support learning processes. Current computer-based learning environments often require explicit representations of large bodies of knowledge, including knowledge of instruction. This book focuses on instructional models as explicit, potentially implementable representations of knowledge concerning one or more aspects of instruction. The book has three parts, relating to different aspects of the knowledge that should be made explicit in instructional models: knowledge of instructional planning, knowledge of instructional strategies, and knowledge of instructional control. The book is based on a NATO Advanced Research Workshop held at the University of Twente, The Netherlands in July 1991.